A study of the actual use of the Thai MOOC open learning service - Kolenberg, Mark Erik Nele; Srisa-An, Chetneti (Edelweiss Applied Science and Technology, 2026)
Access online courses, and they can be studied anywhere, anytime. The Thai government supports the use of Thai MOOC (Massive Open Online Courses) as part of Thailand’s 20-year national strategy to build competitiveness, emphasizing new ways of learning by creating the Thai MOOC Open Learning Service. This platform provides useful information to all users for accessing learning in their fields of interest. Thai MOOC offers a safe environment for individuals from diverse backgrounds to acquire valuable knowledge. This model benefits Thai MOOC by providing a system that offers a clearer picture of overall users, including the Thai Cyber University and lectures within the Thai MOOC system. Data collection and analysis employed a mixed-method approach. Qualitative research involved 21 experts in Thai MOOC, with expert consensus achieved through the rough set Delphi approach. Quantitative research gathered data from 800 actual Thai MOOC users. The analysis utilized both descriptive and inferential statistical methods. The results identified seven key factors: 1) Knowledge Sharing, 2) Thai MOOC Features, 3) Motivation and Usage, 4) Perceived Usefulness, 5) Perceived Ease of Use, 6) Attitude Toward Use, and 7) Actual Use. These factors are essential for Thai MOOC developers to understand user attitudes and improve the platform accordingly.